Angiotensin II inhibition: a potential treatment to slow the progression of sarcopenia. Issue 21 (12th November 2021) - Kingsley, Jeffrey; Torimoto, Keiichi; Hashimoto, Tomoki; Eguchi, Satoru
Abstract: Sarcopenia is defined as the progressive and generalized loss of skeletal muscle mass and strength, which is associated with increased likelihood of adverse outcomes including falls, fractures, physical disability, and mortality. The etiology of sarcopenia has been postulated to be multifactorial with genetics, aging, immobility, nutritional deficiencies, inflammation, stress, and endocrine factors all contributing to the imbalance of muscle anabolism and catabolism. The prevalence of sarcopenia is estimated to range from 13 to 24% in adults over 60 years of age and up to 50% in persons aged 80 and older. As the population continues to age, the prevalence of sarcopenia continues to increase and is expected to affect 500 million people by the year 2050. Sarcopenia impacts the overall health of patients through limitations in functional status, increase in hospital readmissions, poorer hospital outcomes, and increase in overall mortality. Thus, there exists a need to prevent or reduce the occurrence of sarcopenia. Here, we explore the potential mechanisms and current studies regarding angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme (ACE) inhibitors on reducing the development of sarcopenia through the associated changes in cardiovascular function, renal function, muscle fiber composition, inflammation, endothelial dysfunction, metabolic efficiency, and mitochondrial function.